Commentary on: Outcomes of amputation due to long-standing therapy-resistant complex regional pain syndrome type I - Marc Russo; Peter Georgius; Willem Volschenk; Danielle Santarelli (Medical Journals Sweden, 2020)
Missing (Letter)